La notion de parenté épistémique : une modélisation des savoirs entre la pratique des élèves et celle des savants, l’exemple de la danse au collège - Monique Loquet (Recherches en Éducation)
The modelling of knowledge proposed in this paper is based on the theoretical framework of joint action in didactics (JATD). The question is that of meaning: how does knowledge make sense for those who learn it and who teach it? We assume that knowledge takes meaning when it is part of a cultural practice, an oeuvre, a history, a comprehension of the world. The study chooses as an example the teaching of dance in a college which aims the "meeting of oeuvres and artists" in accordance with French school programs. It focuses on the activity of students prompted by the teaching practice, when teaching tries to approach the expert activity. The notion of epistemic kinship between activities of student and artists is central to this study. It revisits the concept of didactic transposition. It raises the question of the proximity (and the distance) between the epistemic capacities developed by students and those evidenced by savants in cultural practices to which the school refers. The conclusions are extended to comparative analyses in didactics.